EVOLUTION OF RADIOCARBON CALIBRATION. Issue 3 (16th June 2022) - Reimer, Paula J
ABSTRACT: In the late 1950s it was recognized that levels of atmospheric radiocarbon ( 14 C) had not been constant over time. Since then, researchers have sought to document those changes, initially through measurements of known age tree rings and more recently using other archives to create curves to correct or calibrate radiocarbon ages to calendar ages. This paper highlights some, but by no means all, of the efforts to create and extend radiocarbon calibration curves.